Special Issue Introduction: Exploring the Lived Experiences of Intra‐EU Mobility in an Era of Complex Economic and Political Change. (29th January 2020) - King, Russell; Pratsinakis, Manolis
Abstract: This paper introduces the special issue on 'Intra‐EU mobilities in times of crisis'. Intra‐EU mobility has emerged as an ambivalent phenomenon. On the one hand, EU‐wide opinion polls still depict freedom of movement as the most positive aspect of European integration. On the other hand, with nationalism and xenophobia on the rise, migration and mobility are increasingly problematized and challenged. Shifting attention from the master narratives about intra‐EU mobility, the aim of the special issue is to bring to the fore the lived experiences of the key actors as recounted in a period of multiple European crises which, in turn, represent the visible and mediatized manifestations of more complex and deep‐seated processes of political and economic change. Here we provide a chronological periodization of intra‐EU mobility trends over recent decades and how they intersect with major geopolitical events, aiming to contextualise the special issue articles which are then presented.